Author Correction: Maintenance, reserve and compensation: the cognitive neuroscience of healthy ageing. Issue 12 (December 2018) - Cabeza, Roberto; Albert, Marilyn; Belleville, Sylvie; Craik, Fergus; Duarte, Audrey; Grady, Cheryl; Lindenberger, Ulman; Nyberg, Lars; Park, Denise; Reuter-Lorenz, Patricia; Rugg, Michael; Steffener, Jason; et al.
In the originally published version of article, there were two errors in the references. The reference "Nilsson, J. & Lövdén, M. Naming is not explaining: future directions for the "cognitive reserve" and "brain maintenance" theories.Alzheimer's Res. Ther. 10, 34 (2018)" was missing. This reference has been added as REF. 14 in the HTML and PDF versions of the article and cited at the end of the sentence "However, over the years, these terms have been used inconsistently, creating confusion and slowing progress." on page 701 and at the end of the sentence "If reserve is defined merely as the factor that individuals with greater reserve have and then this factor is used to explain why some individuals have greater reserve, the argument is clearly circular." on page 704. The reference list has been renumbered accordingly. In addition, in the original reference list, REF. 91 was incorrect. The reference should have read "Cabeza, R. Hemispheric asymmetry reduction in older adults. The HAROLD model.Psychol. Aging 17, 85–100 (2002)". This reference, which is REF. 92 in the corrected reference list, has been corrected in the HTML and PDF versions of the article.